Dual-Signal Colorimetric and Electrochemical Sensor of Dopamine Based on Nanocomposite of Cobalt Oxyhydroxide/Carbon Black. Issue 1 (1st January 2023) - Zou, Xun; Deng, Zilong; Chen, Huiting; Zheng, Zhiyuan; Ji, Limin; Chen, Yuying; Sun, Mingyan; Ouyang, Sixue; Yuan, Zhiying; Zhao, Peng; Tao, Jia
Abstract : In this report, a novel electrochemical and colorimetric dual-mode sensing system was developed for the sensitive and selective detection of DA. The large surface area of CoOOH and the excellent conductivity of CB endow the electrochemical sensing system with high sensitivity. CoOOH with oxidase-like activity will convert the colorless TMB into the blue oxidation product OX TMB, appearing an absorption peak at 652 nm correspondingly. And the addition of DA will inhibit the activity of oxidase followed by a reducing in the absorption. Our device provided a wider detection range for DA from 1 to 30 μ M and 1 to 950 μ M through colorimetric and electrochemical methods, respectively. Furthermore, this biosensor with good biocompatibility has been successfully used for in-vitro tracking of DA efflux from live PC12 cell after being stimulated, which has important scientific and practical value for clinical diagnosis and monitoring.